2015
DOI: 10.1186/s12891-015-0563-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomised trial into the effect of an isolated hip abductor strengthening programme and a functional motor control programme on knee kinematics and hip muscle strength

Abstract: BackgroundDynamic knee valgus and internal femoral rotation are proposed to be contributory risk factors for patellofemoral pain and anterior cruciate ligament injuries. Multimodal interventions including hip abductor strengthening or functional motor control programmes have a positive impact of pain, however their effect on knee kinematics and muscle strength is less clear. The aim of this study was to examine the effect of isolated hip abductor strengthening and a functional motor control exercise on knee ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
33
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 27 publications
3
33
1
2
Order By: Relevance
“…This approach could be called a top-down approach (Barton, Lack, Malliaras, & Morrissey, 2012, Brindle, Mattacola, & McCrory, 2003Brumitt, 2009;Grelsamer & McConnell, 1998;Fredericson & Moore, 2005;Hollman, Kolbeck, Hitchcick, Koverman, & Krause, 2005;Hollman et al, 2006;Powers, 2010;). However, related experimental studies have shown no general support for the concept that strengthening the hip muscles affects the running mechanics such as range of motion and external moments during dynamic tasks (Herman et al, 2008;Willy & Davis, 2011;Palmer et al, 2015) suggesting that the top-down approach does not produce a change in the mechanics of the knee and ankle joint. Another theory concentrates more on the ankle joint and suggests that an increase of strength, especially of the small muscles crossing the ankle joint, should affect movement and moments at the ankle, knee and hip joints (Feltner et al, 1994;Hollman et al, 2005;Tiberio, 1987;).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach could be called a top-down approach (Barton, Lack, Malliaras, & Morrissey, 2012, Brindle, Mattacola, & McCrory, 2003Brumitt, 2009;Grelsamer & McConnell, 1998;Fredericson & Moore, 2005;Hollman, Kolbeck, Hitchcick, Koverman, & Krause, 2005;Hollman et al, 2006;Powers, 2010;). However, related experimental studies have shown no general support for the concept that strengthening the hip muscles affects the running mechanics such as range of motion and external moments during dynamic tasks (Herman et al, 2008;Willy & Davis, 2011;Palmer et al, 2015) suggesting that the top-down approach does not produce a change in the mechanics of the knee and ankle joint. Another theory concentrates more on the ankle joint and suggests that an increase of strength, especially of the small muscles crossing the ankle joint, should affect movement and moments at the ankle, knee and hip joints (Feltner et al, 1994;Hollman et al, 2005;Tiberio, 1987;).…”
Section: Introductionmentioning
confidence: 99%
“…However, many of these suggestions are based on personal opinion/experience rather than on scientific facts. One theory suggests that increased muscular strength around the hip and the core should help to reduce lower extremity joint movement and external joint moments at the lower extremities during running, and thus, reduce the frequency of running injuries (Hott, Liavaag, Juel, & Brox, 2015;Palmer, Hebron, & Williams, 2015;Powers, 2010). This approach could be called a top-down approach (Barton, Lack, Malliaras, & Morrissey, 2012, Brindle, Mattacola, & McCrory, 2003Brumitt, 2009;Grelsamer & McConnell, 1998;Fredericson & Moore, 2005;Hollman, Kolbeck, Hitchcick, Koverman, & Krause, 2005;Hollman et al, 2006;Powers, 2010;).…”
Section: Introductionmentioning
confidence: 99%
“…The vast majority of programs focus on many often complex exercises not only strengthening but also stretching or equivalent [13][14][15]. The problem in implementing the home exercise plan that the participants report is the time they have to spend.…”
Section: Introductionmentioning
confidence: 99%
“…Palmer et al 2015 and Patrek et al 2011 research focusing on valgus 3D assessment determined a 3positive change as clinically significant and representative. The researchers used a one-leg landing test to assess, which due to a similar motion pattern can be compared to a one-leg squat test in the context of valgus assessment[14,30].In addition, Palmer et al 2015, using the hip abduction exercise strengthening the gluteal muscles over a 6 week period in military personnel, showed a high tendency to decrease valgus by 5˚ defined as clinically significant, but not statistically significant. Intervention group performed exercises focused on strengthening hip abductors[14].Video analysis showed mean of knee valgus angle at the pre-training stage for the left leg CON group (18˚±9.7 ˚), INT (16.1˚±10.5 ˚) and for right leg CON (18.5˚±12.0 ˚), INT (1.3 ˚±11.8˚).…”
mentioning
confidence: 99%
“…Por otro lado, la ganancia de fuerza muscular está relacionada con la mejora del control motor y de la activación neuromuscular en trabajos de un mínimo del 40-60% con respecto a la contracción máxima voluntaria (11,12). La activación muscular isométrica se relaciona con los mecanismos de control motor mejorando la eficacia del acoplamiento de información entre los propioceptores musculares, y con los efectores motores centrales (13,14).…”
Section: Introductionunclassified